2020
DOI: 10.1609/aaai.v34i01.5476
|View full text |Cite
|
Sign up to set email alerts
|

MaskGEC: Improving Neural Grammatical Error Correction via Dynamic Masking

Abstract: Grammatical error correction (GEC) is a promising natural language processing (NLP) application, whose goal is to change the sentences with grammatical errors into the correct ones. Neural machine translation (NMT) approaches have been widely applied to this translation-like task. However, such methods need a fairly large parallel corpus of error-annotated sentence pairs, which is not easy to get especially in the field of Chinese grammatical error correction. In this paper, we propose a simple yet effective m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Kiyono et al demonstrated that the back-translation approach is effective to enlarge the training data to improve the correction performance, compared with directly introducing the noise to build the training data [41]. Zhao et al proposed a method to improve the grammar error correction model based on neural machine translation through dynamic masking, which solves the model's need for a corpus of "error-correct" sentence pairs [42].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiyono et al demonstrated that the back-translation approach is effective to enlarge the training data to improve the correction performance, compared with directly introducing the noise to build the training data [41]. Zhao et al proposed a method to improve the grammar error correction model based on neural machine translation through dynamic masking, which solves the model's need for a corpus of "error-correct" sentence pairs [42].…”
Section: Related Workmentioning
confidence: 99%
“…As for comparison on the shared GEC task of NLPCC 2018, the MaxMatch(M²) Scorer [42,51] is introduced to evaluate the performance of competitors. It allows the phrases from the prediction sentence with the maximal overlap with the gold standard to be selected to form the set of prediction edits { , … }.…”
Section: Evaluation Criteriamentioning
confidence: 99%
“…In the case of China, which is an East Asian cultural region such as Korea, there is a lack of corpus to be used for GEC learning, like Korean. So, in the case of Zhao and Wang [14], the method of giving noise was overcome by applying the dynamic masking technique.…”
Section: Related Workmentioning
confidence: 99%
“…Early studies (Gamon et al, 2008;Tetreault et al, 2010;Dahlmeier and Ng, 2011;Berend et al, 2013;Rozovskaya and Roth, 2014) take GEC as a classification task and rely much on hand-crafted rules. More recently, the techniques of statistical machine translation and neural machine translation are applied to GEC and have made remarkable performance (Behera and Bhattacharyya, 2013;Junczys-Dowmunt and Grundkiewicz, 2016;Junczys-Dowmunt et al, 2018;Chollampatt and Ng, 2018;Zhao et al, 2019;Awasthi et al, 2019;Kiyono et al, 2019;Kaneko et al, 2020;Omelianchuk et al, 2020;Zhao and Wang, 2020).…”
Section: Related Workmentioning
confidence: 99%